BODY IMAGE PERCEPTION OF PRACTICING ADOLESCENTS OF PHYSICAL ACTIVITY OF A SCHOOL OF PRIVATE NET OF TEACHING, RIO DE JANEIRO. (Fiep Bulletin - online, 2013)
Current studies on body image point to damages made a list to the dissatisfaction, depreciation, distortion and preoccupation with the self-image, when cultural-partner was strongly influenced by factors. These factors, when the influence of the media was associated, can bring in disturbances in the nutritional status. It was aimed describing of body self-referred and9 wanted image perception of adolescent practicing students of physical activity of a school of the private net of teaching, Rio de Janeiro. It the question is a descriptive study carried out with adolescents when series of the basic teaching were enrolled in 5th and 6th, with ages between 10 and 14 years, in August of 2006. For the evaluation of the perception of the body self-referred and wanted image, there was used the Scale of Silhouettes of the Human Figure proposed by Stunkard et al. (1983). The statistical analysis was done when 10.0 are used the statistical packet SPSS version. Of 50 evaluated adolescents, 62% was girls, with middle age of 11,50,8 years and the boys with average of age of 11,60,8 years. While analyzing the body self-referred and by the classification of the nutritional status of the scale of silhouettes, it was detected that 58,1 % of the girls self-referred weight adequate, 25,8% with surcharge and 16,1% with low weight. As for physical wanted image, 71,7% was wanting to be weight adequate, meantime, 29% they would like having low weight. Regarding the boys, 57,9% self-referred weight adequate, 31,6% with surcharge and 10,5% with low weight, meantime, they all were wanting to be eutrophics it could be ended that approximately 60% of the evaluated population auto-told to itself to have ideal weight. Nevertheless, it was detected between the girls, a wish of having weight below that which they really had. Key-Words: Adolescents, Nutritional
Keywords: Adolescents; Nutritional Status; Body Image